Development of UTAYA: Implementing Snakes and Ladders Media for Contextual Teaching and Learning of Forces in Physics Education - Riska Kartikaningrum; Petra Kristi Mulyani (Jurnal Penelitian Pendidikan IPA, 2024)
Conventional learning and limitations in learning media made students passive in learning, which resulted in students' lack of interest in learning and achievement. This research aimed to develop innovative, technology-based instructional media, and to determine the validity and effectiveness of UTAYA, snakes and ladders media for contextual teaching and learning (CTL) of forces in fourth-grade. The research was developed using the Borg and Gall model. UTAYA was categorized as very appropriate for use with a validity percentage of 93% media experts, meaning that the media presented was interesting and appropriate to the content, easy to use by teachers and students, practical and fun, and had an appropriate appearance to the students’ level of development and character, Content experts validated and assessed the accuracy of the content of the media in the very appropriate category with a percentage of 91%, which meant that the content presented was appropriate to the learning objectives and made it easier for students to understand the content. The forces topic content was covered entirety in the media, stimulated students' curiosity, which was appropriate to support learning and increase students' knowledge, it used of appropriate language, according to students' development.  Based on the pretest and posttest results, UTAYA was effective to improve learning outcomes, as seen from the effectiveness of the t-test and Ngain tests. The t-test showed a Sig. <0.05, meaning there was a significant difference between learning outcomes before and after treatment. The N-gain test showed a medium criterion, 0.70 on a large-scale test, and a medium criterion, 0.64 on a small-scale test, that the students were very enthusiastic and could understand the lesson. From these results, UTAYA was valid and effective to be an instructional media to improve learning